GSTM1 null genotype underpins recurrence of NF2 meningiomas - Johnson, Anthony C.; Tsitsikov, Erdyni N.; Phan, Khanh P.; Zuccato, Jeffrey A.; Bauer, Andrew M.; Graffeo, Christopher S.; Hameed, Sanaa; Stephens, Tressie M.; Liu, Yufeng; Dunn, Gavin P.; Tsytsykova, Alla V.; Jones, Pamela S.; et al. (Frontiers in Oncology, 2024)
IntroductionMeningiomas are the most common primary central nervous system (CNS) tumor in adults, comprising one-third of all primary adult CNS tumors. Although several recent publications have identified molecular alterations in meningioma including characteristic mutations, copy number alterations, and gene expression signatures, our understanding of the drivers of meningioma recurrence is limited.ObjectiveTo identify gene expression signatures of 1p-22q-NF2- meningioma recurrence, with concurrent biallelic inactivation of NF2 and loss of chr1p that are heterogenous but enriched for recurrent meningiomas.MethodsTranscriptomic alterations present in recurrent versus primary 1p-22q-NF2- meningiomas were identified using RNA sequencing (RNA-seq) data in a clinically annotated cohort.ResultsRecurrent 1p-22q-NF2- meningiomas were enriched for a newly identified GSTM1 null genotype compared to primary meningiomas that showed variable GSTM1 expression and independent external validation was performed.ConclusionsThe GSTM1 null genotype is a novel biomarker of 1p-22q-NF2- meningioma recurrence that resolves heterogeneity in existing meningioma subtypes and may be used to guide future clinical management decisions on extent of treatment to improve patient outcomes.